2007
DOI: 10.1016/j.apm.2005.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of a sheet/cloud cavitation on a NACA0015 hydrofoil

Abstract: A single fluid model of sheet/cloud cavitation is developed and applied to a NACA0015 hydrofoil. First, a cavity formation model is set up, based on a three-dimensional (3D) non-cavitation model of Navier-Stokes equations with a large eddy simulation (LES) scheme for weakly compressible flows. A fifth-order polynomial curve is adopted to describe the relationship between density coefficient ratio and pressure coefficient when cavitation occurs. The Navier-Stokes equations including cavitation bubble clusters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…This, in turn, implies that the input data to the acoustic analogy becomes corrupted, making its predictions incorrect. Studies involving compressible flow simulations, such as those by Wang & Ostoja-Starzewski (2007) and Seo et al (2008), have reported that far more physical results may be obtained if the incompressible assumption is not invoked. However, undertaking compressible simulations of marine problems is still an uncommon practice and, reportedly, may be associated with significantly increased computational costs (Wikstrom 2006, Godderidge et al 2009, Budich et al 2015, Fujiyama 2015.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, implies that the input data to the acoustic analogy becomes corrupted, making its predictions incorrect. Studies involving compressible flow simulations, such as those by Wang & Ostoja-Starzewski (2007) and Seo et al (2008), have reported that far more physical results may be obtained if the incompressible assumption is not invoked. However, undertaking compressible simulations of marine problems is still an uncommon practice and, reportedly, may be associated with significantly increased computational costs (Wikstrom 2006, Godderidge et al 2009, Budich et al 2015, Fujiyama 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Their numerical results were in good agreement with the experiment, and presented various cavitation details and mechanisms. Moreover, some favorable results have also been published (Dittakavi et al, 2010;Huang et al, 2014;Ji et al, 2013Ji et al, , 2015Roohi et al, 2013;Wang and Ostoja-Starzewski, 2007;Wang et al, 2016aWang et al, , 2016b. Besides, some new approaches are developed to simulate the cavitating flow and get favorable results (Ma et al, 2010;Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…LES with the WALE SGS stress model was adopted to calculate the cavitation shedding and horse-shoe structures by Ji et al [22][23][24] and Huang et al [25]. A single fluid model of sheet/cloud cavitation was developed and applied to a NACA0015 hydrofoil by Wang [26]. The physical mechanism for the cavitation induced pressure fluctuations around a NACA66 hydrofoil was analyzed by Ji et al [27].…”
Section: Introductionmentioning
confidence: 99%